(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Revolutionizing traditional teaching methods in this scientific article. Flipped learning, a teaching method that has gained a lot of attention in recent years, is revolutionizing traditional teaching methods. This innovative pedagogical practice involves transferring learning content from classroom lectures to out-of-class activities such as online videos or readings.